Law No. 1 Of The Year 2018 Amending Certain Provisions of Law No. 59 of the Year 1979 On Establishing the New Urban Communities = قانون رقم 1 لسنة 2018 بتعديل بعض أحكام القانون رقم 59 لسنة 1979 فى شأن إنشاء المجتمعات العمرانية الجديدة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic